Effect of Sechium edule on chemical induced kidney damage in experimental animals - Sayeed Mohammed Firdous Mumtaz; Shounak Paul; Anupam Kanti Bag (Bangladesh Pharmacological Society, 2012)
The aqueous extract of leaves of Sechium edule was evaluated for its protective activity against gentamicin, potassium dichromate-induced nephrotoxicity and streptozotocin-induced diabetic nephropathy in experimental animals. In these three conditions, the extract of S. edule (200 mg/kg) has significantly (p<0.001) decreased the level of blood urea, blood urea nitrogen and serum creatinine and also significantly (p<0.001) increased the serum levels of total protein. The serum uric acid level was also significantly (p<0.001) decrease in diabetic mice treated with the extract (200 mg/kg).  The extract also improves the histology of the kidney. The results indicate that aqueous extract of leaves of S. edule has possessed protective effect against gentamicin- and potassium dichromate-induced nephrotoxicity and streptozotocin-induced diabetic nephropathy in experimental animals.